THE INFLUENCE OF PRINCIPAL'S ROLE AND WORK MOTIVATION TO TEACHERS JOB SATISFACTION - Fajar Defitrika; Fitri Nur Mahmudah (International Journal of Educational Management and Innovation, 2021)
Job satisfaction as a support for the implementation of teacher's functional tasks is still lacking. Based on preliminary observations, it is thought that this was caused by the lack of the principal's role and work motivation. Therefore, this study aims to uncover the influence of the principal's role and work motivation on the job satisfaction of public middle school teachers. The hypotheses of this study are: (1) The principal's role influence the job satisfaction of public middle school teachers, (2) The work motivation influence the job satisfaction of public middle school teachers, (3) Principal's role and work motivation together influence the job satisfaction of public middle school teachers. This study uses a survey method with a quantitative approach, correlational and regression techniques—data collection techniques through a Likert scale questionnaire of 59 respondents who are teachers of public middle school. The results of data analysis show that (1) the principal's role influences the job satisfaction of public middle school teachers, (2) Work motivation influences the job satisfaction of public middle school teachers, (3) Principal's role and work motivation together influences the job satisfaction of public middle school teachers. Based on these findings, the authors suggest that some improvement efforts can be made, especially in increasing teacher job satisfaction, including involving teachers in further education and providing encouragement to start creatively and achieving, mobilizing the learning outcome evaluation team, and following the development of science. , technology, and the arts, exemplify good models of learning and counselling.